Peran Sifat Shiddiq Terhadap Good Governance Dalam Meningkatkan Kepercayaan Nasabah PT Permodalan Nasional Mandiri Cabang Jombang - Febrianto, Mochammad Vanny; Nisa, Bella Khoirun; Djasuli, Mohamad (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
This study aims to find out how well the corporate governance that has been implemented by the company at PT Permodalan Nasional Mandiri Mekaar Jombang Branch in increasing customer trust. In this method, the research method uses a descriptive approach that takes the research location from the Jobang branch of PT Permodalan Nasional Mandiri customers. Source of data used in this research is secondary data. This analysis uses the principle of leadership, namely shiddiq (honest). This research is still relatively rare so the concept of Islam needs to be done. Customers think that PNM Mekaar's services are good enough, but still need to be developed so that customers feel safer when borrowing money.